My years with general motors - Alfred P Sloan; SLOAN (Alfred P); McDONALD (John) Ed; STEVENS (Catherine) Ed (London: Pan Books Ltd, 1963)
My Years with General Motors is a modern classic for those who love management books. After it was published the book went on to become an immediate success and made its way to The New York Times bestseller list. This book is written by Alfred Sloan and editions in Portuguese and Polish are also available. During his fifty years in General Motors, Sloan achieved some of the most impossible triumphs. Alfred Sloan took over the company in the first half of 1920's when it was experiencing a great downturn. Till he took over, the company was going through heavy losses but within the next decade the tables turned drastically, with General Motors soaring high with profits. The book is divided into two parts. The first part is about the consistent progress of the GM including the development and origin of the company. The first part describes the steady growth of the company and its relevance and impact on the automobile industry. The second part describes the details of the different segments like distribution, engineering, overseas operations, defense products and the war. Through the years since its release in 1964 the book has been providing insight on the perfected levels of management and leadership experience by an industrial stalwart, Alfred Sloan. The reissue edition of My Years with General Motors was published by RHUS in 1990 and is available in paperback. Key Features: This business book has received praise from stalwarts like Bill Gates. Its inspiring details about General Motors have motivated and encouraged many managers.
Keywords: Economics; Automobile Markets